TPACK Analysis of 7th Grade English Teacher in Merdeka Curriculum at Sukaraja Commissariat - Persada, Intan Dwi; Mutiara, Dewi; Jamil, Ikram (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The importance of technology skills for teachers in the educational process, particularly in teaching English, prompted this research. The Merdeka Curriculum enables teachers to incorporate technology into their lessons. The purpose of this study is to find out TPACK competence, TPACK level, and the factors that hinder 7th Grade English teachers in the Merdeka Curriculum at Sukaraja Commissariat, Sukabumi Regency. This research is a qualitative descriptive approach with data drawn from surveys, interviews, and classroom observations. The results indicated that teachers were at different levels of technological sophistication, with the majority being in the